The Growing Dictionary of the Slovenian Language (2014-) and Slovenian Neologisms: Study on Types of Data and Their Use - Domen Krvina (Slovenski Jezik - Slovene Linguistic Studies, 2023)
The article aims at presenting the methods of detection of Slovenian neologisms, used in the making of the Growing Dictionary of the Slovenian Language, accessible at the Fran portal <https://fran.si/>, which integrates various dictionaries into a single whole, form 2014 onwards. In the first year of compiling and for the following few years, the main source of the candidates was corpus Gigafida 1.0, built in 2013. Due to the corpus not being updated regularly (and unavailability of other appropriate sources), users’ suggestions have taken over the main role. Users submit suggestions directly on the Fran portal. The corpus Gigafida and other (Janes, SlWaC) are still used for checking users’ suggestions. Due to a high number of such suggestions and a growing demand for new lexical descriptions, their importance cannot be overlooked. The neologisms collected in the dictionary exhibit a number of characteristics, a brief overview of which is provided at the end of the study.